Effects of Ag addition and Ag3Sn formation on the mechanical reliability of Ni/Sn solder joints. (August 2017) - Chu, Kunmo; Lee, Changseung; Park, Sung-Hoon; Sohn, Yoonchul
Abstract: Formation of intermetallic compounds (IMCs) in solder joints is closely associated with the mechanical reliability of the system. Though internal voids formed in Ni/Sn solder joints are known to be related to the formation of Ni3 Sn4 IMC, a detailed study on the mechanical reliability has not yet been reported. In this study, the mechanical reliability of Ni/Sn joints was investigated using two different soldering systems: Ni/Ag-Ag/Sn/Ni bilayers and Ni/Sn/Ag-Ag/Sn/Ni sandwich structures. The failure mode was found to be closely related to the formation and growth of an Ag3 Sn phase. Filling of the voids with Ag3 Sn IMC resulted in maximum shear strength, with a failure locus through Ni3 Sn4 and Ag3 Sn. However, formation of a large amount of Ag3 Sn decreased the shear strength once again. Graphical abstract: Highlights: Effect of Ag addition on mechanical reliability of Ni/Sn joint was investigated. Failure mode of Ni/Sn joint was closely related with void filling of Ag3 Sn intermetallic compound. Maximum shear strength was obtained with the failure locus through Ag3 Sn and Ni3 Sn4 . To acquire optimum shear strength, amount of Ag added is of great importance.